PENGUKURAN KINERJA SUPPLY CHAIN CUMI-CUMI DI PPS NIZAM ZACHMAN BERDASARKAN MODEL MATURITY MENGGUNAKAN METODE SCOR - Muhajirin Muhajirin; Novi Sofia Fitriasari; Ayang Armelita Rosalia (Jurnal Informatika Kaputama (JIK), 2023)
The supply chain system is an important factor in the commodity process or an effective and efficient logistics system. In the field of the fishing industry, the supply chain system greatly influences the process of activity flow starting from fish availability, productivity, fish quality assurance to distribution to consumers. Effective and efficient supply chain system management will have a huge impact on the commodities of the national fishing industry. Therefore, the purpose of this study is to measure the performance of the supply chain management systembased on the level of maturity so that it can be a benchmark as an improvement in the future. The approach method used in this study is to use the concept of the Supply Chain Operation Reference (SCOR) model which is collaborated with key performance indicators (KPI) andanalytical hierarchy processes (AHP) to produce the maturity value of supply chain performance. This research uses a descriptive method by making observations, distributing instruments in the form of questionnaires, interviews and literature studies in its preparation. The results of the study obtained a level of supply chain performance in PPSNZJ obtained a final value of 84.38 by entering the Good performance category based on the SCOR method and the supply chain maturity level obtained a maturity level of 4.3 on a scale of 0-5 with managed and measurable conditions. Efforts to measure supply chain performance are carried out to realize the improvement of supply chain performance in the national fishing industry which is integrated with suppliers, fishermen, companies, stakeholders and consumers.